Free Solution Convection at Non-Isothermal Evaporation of Aqueous Salt Solution on a Micro-Structured Wall; Nanoscale and Microscale Thermophysical Engineering; Vol. 19, iss. 1 - Misyura S. Ya. Sergey Yakovlevich (2019, 2019)
Title screen